LEGAL ANALYSIS OF THE PRINCIPLE OF FREEDOM OF CONTRACT TOWARDS LEGAL CERTAINTY AND JUSTICE IN AN AGREEMENT - Tumpal Haojahan Sihombing; Muh Amin Saleh; Muhenri Sihotang; Appe Hutauruk (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze the implementation of the principle of freedom of contract in Indonesian positive law and its implications for legal certainty and justice for the parties in an agreement. The main focus of this study is directed at how to balance individual autonomy (party autonomy) with legal protection for parties with weaker bargaining power, especially in the use of standard contracts. The research method used is normative juridical with a statute approach and a conceptual approach. Data were collected through a literature study of primary legal materials such as the Civil Code and relevant secondary and tertiary legal materials. The results of the study indicate that the implementation of the principle of freedom of contract as regulated in Article 1338 paragraph (1) of the Civil Code has provided legal certainty through the principle of pacta sunt servanda. However, in practice, this legal certainty is often formalistic and tends to benefit parties who are economically and informationally dominant. Substantive justice is often neglected when freedom of contract is used as an instrument of exploitation through disproportionate exoneration clauses. This study concludes that freedom of contract is not absolute, but must be limited by the principles of good faith, propriety, and public order in order to create a balance of rights and obligations that is just for all parties.